Landslides glissements de terrain - Senneset, Kaare; International Symposium on Landslides (7th : 1996 : De Terrain) (Rotterdam : A A Balkema, 1996)
Vol.1. Assessment and management of landslide risks and hazards, Landslides in sensitive and metastable materials, Shoreline stability and submarine slides -- Vol.2. Landslide investigations, Slope instability in seismic areas, Slope instability in tropical areas, Stability analyses and geotechnical parameters -- Vol.3. Early warning,monitoring and instrumentation, Stability analyses and performance of open pit mine slopes, Stabilization and remedial works, Analysis of landslide inventories